TECHNOLOGIES FOR IMPROVING THE FORMATION OF PROFESSIONAL COMPETENCE OF STUDENTS ON THE BASIS OF A CREATIVE APPROACH - A. A. Akromov; Adizova Gulzoda Mehridinovna (Galaxy International Interdisciplinary Research Journal, 2022)
In the modernization of education, great importance is attached to the formation of professional competence as a controlled process in assessing professionalism. In active educational methods, the formation of the technology of professional competence of a specialist plays a role. The unit of learning task is a problem situation. The use of active teaching methods allows students to effectively prepare for professional activities. Under the influence of this activity, the process of assimilation by students of educational material arises and is realized, the set goal is achieved, a complex of methods for the formation of professional competence is revealed.